The Influence of YouTube Learning Media with Observation Method and Self-Confidence on Learning Outcomes of Heavy Equipment Technology - Wagino Wagino; Ambiyar Ambiyar; Nurhasan Syah; Suhendar Suhendar; Iffarial Nanda (Universitas Sultan Ageng Tirtayasa, 2021)
This study aims to determine the effect of YouTube media with the observation method and self-confidence on learning outcomes of Heavy Equipment Technology. The population in this study were students in 2019 in the Automotive Engineering Department, Faculty of Engineering, Universitas Negeri Padang with a sample of 32 students in the experimental group and 32 students in the control group. Samples were taken by cluster sampling technique. Data were collected through validated tests. The data analysis technique used the two-way variance test (ANOVA) and Tukey test. Before testing the hypothesis, the normality test and homogeneity test were carried out first. The results of data analysis showed that YouTube learning media and confidence in learning outcomes in the Heavy Equipment Technology course obtained a higher interaction with the results of the analysis of variance for the calculated F value = 4.24> F table = 3.97 at a significant level = 0.05. Thus, YouTube learning accompanied by high self-confidence obtains better learning outcomes compared to learning the observation method.